The Correlation of Students’ Communication and Collaboration Skills to Work Ethics through Project-Based Learning - Lianto, Lianto; Rohayati, Yulista Trias; Lestari, Sri Rahayu (Tecno Scientifica Publisher, 2026)
Effective communication and collaboration were vital competencies that students needed to master to enhance their work ethic in the 21st century. This study sought to investigate the relationship between communication, teamwork, and work ethic qualities in the context of Project-Based Learning (PBL). The sample for this study comprised students enrolled in an introductory immunology course at the Faculty of Biology, Malang State University, Indonesia. Data were analyzed using multiple regression and correlation analysis. The findings indicated a correlation among communication, collaboration, and work ethic skills. Communication and teamwork contributed 61.5% to students' work ethic skills in project-based learning. The project-based learning style was crucial for enhancing students' communication and collaboration abilities. Project-based learning also influenced students' work ethic. It was strongly recommended to implement the project-based learning approach in higher education institutions to enhance students' 21st-century competencies.